1996
DOI: 10.1007/bf00005016
|View full text |Cite
|
Sign up to set email alerts
|

Selective ingestion of detritus by a north temperate omnivorous fish, the juvenile white sucker, Catostomus commersoni

Abstract: SynopsisThe capacity of the juvenile white sucker, Catostomus commersoni, to feed selectively on detritus was examined by analyzing gut contents of fish feeding in a northern Michigan pond and in laboratory aquaria. Suckers selected fine particle detritus. The median length of detritus particles consumed by pond suckers ranged from 26-38 pm for all seasons sampled. Although suckers in the pond ingested invertebrates > 21.5 urn they never ingested detritus particles > 215 urn. Suckers fed pond detritus in labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…The six species of loricariids studied here had well-developed gill rakers when compared with other species of the same family with similar feeding habits, such as Loricaria vetula Valenciennes (=Paraloricaria vetula) and Loricariichthys platymetopon Isbrü cker & Nijssen (Angelescu & Gneri, 1949;Fugi, 1993), yet they were similar to other loricariids such as Loricaria anus Valenciennes (=Loricariichthys anus), Hypostomus plecostomus L. and H. hoplonites Py-Daniel (Py-Daniel, 1984), that feed on small-sized particles by straining ingested food (Bowen, 1983;Verigina, 1990;Ahlgren, 1996). Rhinelepis aspera has a branchial apparatus that is modified and different from that of other species.…”
Section: Discussionmentioning
confidence: 93%
“…The six species of loricariids studied here had well-developed gill rakers when compared with other species of the same family with similar feeding habits, such as Loricaria vetula Valenciennes (=Paraloricaria vetula) and Loricariichthys platymetopon Isbrü cker & Nijssen (Angelescu & Gneri, 1949;Fugi, 1993), yet they were similar to other loricariids such as Loricaria anus Valenciennes (=Loricariichthys anus), Hypostomus plecostomus L. and H. hoplonites Py-Daniel (Py-Daniel, 1984), that feed on small-sized particles by straining ingested food (Bowen, 1983;Verigina, 1990;Ahlgren, 1996). Rhinelepis aspera has a branchial apparatus that is modified and different from that of other species.…”
Section: Discussionmentioning
confidence: 93%
“…We also measured stable S isotopes in fish species that feed, as adults, mainly on detritus and benthic invertebrates ( Catostomus commersoni ; Ahlgren, 1996) or on fish ( Esox lucius ; Skov et al. , 2003).…”
Section: Resultsmentioning
confidence: 99%
“…4), whereas in Lakes É vain and Fortune bivalves were significantly depleted in 13 C compared to insects, and in Lake Ollier the d 13 C values of bivalves differed from those in Hexagenia but not those of Sialis (significance level of 0.05 for all comparisons; A N O V A A N O V A and Tukey post hoc tests). We also measured stable S isotopes in fish species that feed, as adults, mainly on detritus and benthic invertebrates (Catostomus commersoni; Ahlgren, 1996) or on fish (Esox lucius; Skov et al, 2003). Indeed, stable N isotopes confirmed that C. commersoni is at a lower trophic level than E. lucius in all of our study lakes; that is, mean (±SD) trophic positions of the two species were 2.0 ± 0.3 and 2.7 ± 0.2, respectively, as determined by comparing N isotopic values in fish and in the bivalve P. grandis (Cabana & Rasmussen, 1996).…”
Section: Resultsmentioning
confidence: 99%
“…In both temperate and tropical aquatic systems, diverse and often locally abundant invertebrate and vertebrate detritivores are adept at selectively feeding on the most labile and nutritionally rich fractions of detritus (Arsuffi & Suberkropp 1985; Wallace et al. 1987; D’Avanzo, Alber & Valiela 1991; Maltby 1994; Ahlgren 1996; Wilson et al. 2003).…”
Section: Introductionmentioning
confidence: 99%
“…In both temperate and tropical aquatic systems, diverse and often locally abundant invertebrate and vertebrate detritivores are adept at selectively feeding on the most labile and nutritionally rich fractions of detritus (Arsuffi & Suberkropp 1985;Wallace et al 1987;D'Avanzo, Alber & Valiela 1991;Maltby 1994;Ahlgren 1996;Wilson et al 2003). Morphic detritus, including coarse particulate organic matter such as allochthonous leaves and wood, is consumed by few fishes in temperate stream systems -some Asian carps (Ctenopharyngodon idella, Hypophthalmichthys nobilis and H. moltrix) being exceptions (Cremer & Smitherman 1980;Prinsloo & Schoonbee 1987) -but is specialized on by diverse assemblages of macroinvertebrates collectively referred to as shredders (Cummins 1973;Peterson & Cummins 1974;Cummins & Klug 1979;Maltby 1994).…”
Section: Introductionmentioning
confidence: 99%